2016
DOI: 10.2139/ssrn.2814748
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Education and Training: A Pathway to the Straight and Narrow

Abstract: Education is often claimed to reduce social exclusion and crime, yet there is little empirical evidence beyond that for increased schooling. In this study, we estimate the crime-reducing effects of participating in post-secondary vocational education and training (VET) between ages 16 and 44, exploiting a natural experiment in Australia that increased VET participation in the state of Victoria, but not in the neighbouring state of New South Wales. Using postcode (zipcode) level administrative data and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Researchers in Russia found that TVET reduced the risk of youth unemployment (Blinova et al, 2015). Other studies similarly revealed that TVET participants had fewer new crime reconvictions (Bouffard et al, 2000;Jha & Polidano, 2016).…”
Section: Tvet Valuesmentioning
confidence: 96%
See 1 more Smart Citation
“…Researchers in Russia found that TVET reduced the risk of youth unemployment (Blinova et al, 2015). Other studies similarly revealed that TVET participants had fewer new crime reconvictions (Bouffard et al, 2000;Jha & Polidano, 2016).…”
Section: Tvet Valuesmentioning
confidence: 96%
“…In the long term, tax income increases from higher earnings with increased employment and productivity (Hoeckel, 2008). Studies also show plausible causal evidence of the effect of TVET on the reduction of crime rate (Jha & Polidano, 2016). All of these public values are derived from those created by individuals and enterprises.…”
Section: Tvet As a Service Systemmentioning
confidence: 99%